2003
DOI: 10.1080/0268869031000153071
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic epidural haematoma of the posterior fossa in childhood: 16 new cases and a review of the literature

Abstract: A series of 16 children (nine males, seven females) with traumatic epidural haematoma of the posterior fossa (TEHPF) is presented. All patients had a history of mild to moderate trauma to the occiput. The causes were falls in 15 and traffic accident in one case. Four of the 16 cases had depressed fractures of the occipital bone. Surgical intervention was performed in all cases. In 14 patients the outcome was good, one patient had moderate disability and one died. Our study revealed that early diagnosis and urg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 8 publications
7
32
0
3
Order By: Relevance
“…The surgical team should be technically ready for dural sinus repair, and a strong pediatric anesthesia support should be available to manage air embolism and to replace significant blood loss during surgery. Berker et al [8] have recommended surgery in all cases even if the neurological condition was stable. However, Wong [9] had observed that patients with a PFEDH volume less than 10 ml, thickness no more than 15 mm, a midline shift of no more than 5 mm and in the absence of significant intracranial hematoma elsewhere on CT scan undergoing conservative management achieve the same excellent outcome as those undergoing early surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical team should be technically ready for dural sinus repair, and a strong pediatric anesthesia support should be available to manage air embolism and to replace significant blood loss during surgery. Berker et al [8] have recommended surgery in all cases even if the neurological condition was stable. However, Wong [9] had observed that patients with a PFEDH volume less than 10 ml, thickness no more than 15 mm, a midline shift of no more than 5 mm and in the absence of significant intracranial hematoma elsewhere on CT scan undergoing conservative management achieve the same excellent outcome as those undergoing early surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Associated occipital fractures are usually present [8]. Symptoms and signs are often varied, and no consistent clinical profile could indicate an evolving PFEDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transverse sinus collects blood from the superior sagittal sinus, straight sinus, great cerebral vein, cerebral vein, and other blood vessels, but its sinus pressure is 50% smaller than other sinus (3)(4). If the transverse sinus is compressed, causing venous return disorder, the symptoms of intracranial hypertension can be significant and can rapidly form tonsillar herniation, which is difficult to resolve, even with strong dehydration and hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The condition may rapidly deteriorate, causing compression of the transverse sinus and brain stem and subsequently death of the patient (1)(2)(3)(4)(5)(6)(7)(8)(9). This type of epidural hematoma mainly occurs due to occipital deceleration injury, most often associated with occipital bone fracture or lambdoid suture separation (3)(4). Venous sinus detachment, meningeal blood vessels leakage, and a fracture line across the transverse sinus all lead to SIDEH (3).…”
Section: Discussionmentioning
confidence: 99%